Developing Android-Based Mobile Application for Learning Procedure Text - Sa'adah, Kimiyaul Laili; Shofi, Ahmad Thoyyib (IKIP Siliwangi, 2025)
The advancement of technology has transformed education, providing opportunities for innovative learning methods. This study aims to develop an Android-based mobile application to support the learning of procedure texts for Grade X students at MA Assa’adah, aligned with the Merdeka Curriculum. Current teaching practices still rely on conventional methods, such as textbooks and manual translation using Google Translate. These approaches often limit vocabulary development and hinder students from achieving the expected competency standards (KKM). To address these challenges, the proposed application integrates procedure text materials with multimedia features, including images and audio, to enhance interactivity, engagement, and motivation in learning. The research employs the Research and Development (R&D) approach, following the PLOMP model. Data were gathered through questionnaires administered to students and interviews with the teacher. The findings indicate that the developed mobile application serves as an innovative and accessible tool, improving students’ comprehension of procedure texts and supporting English language learning. Teacher observations confirmed increased student motivation and participation during lessons.